Quenching Phase Separation by Vapor Deposition Polymerization. Issue 1 (15th October 2015) - Tao, Ran; Anthamatten, Mitchell
Abstract : The formation of porous polymer by a template‐free, vapor deposition method is studied. Liquid–liquid phase separation of deposited species is quenched by the formation of chemical cross‐links. The resulting morphology depends on the relative rates of polymerization, cross‐linking, and phase separation. The use of a highly immiscible, liquid porogen results in open‐cell, macroporous structures. If an immiscible and crystallizable porogen is employed, porous materials grow as scaffolds of interconnected sheets. The relationship between process conditions and resulting pore‐shape and size is evaluated. The ability to control porous polymer growth, morphology, and density can be used in applications to tune modulus and damping characteristics, biological function, or drug delivery at small scales. Abstract : A template‐free method is applied to fabricate continuous‐phase, porous polymer films by simultaneous phase separation during vapor deposition polymerization. Experiments show that the morphology and porosity of the as‐deposited polymer thin films depend on deposition rate, cross‐linker density, the mass transfer mobilities of phase‐separating species, and the interaction energies between species.